Emergency department discharge instruction for mild traumatic brain injury: evaluation on readability, understandability, actionability and content - Abdul Rahman, Nurul 'Inayati; Nurumal, Mohd. Said; Awang, Mohamed Saufi; Mohd. Shah, Aida Nur Sharini (Elsevier, 2020)
Introduction: Emergency departments (EDs) routinely provide discharge instructions due to a large num- ber of patients with mild traumatic brain injury (mTBI) being discharged home directly from ED. This study aims to evaluate the quality of available mTBI discharge instructions provided by EDs of Malaysia government hospitals. Methods: All 132 EDs were requested for a copy of written discharge instruction given to the patients. The mTBI discharge instructions were evaluated using the Patient Education Materials Assessment-Printable Tool (PEMAT-P) for understandability and actionability. Readability was measured using an online read- ability tool of Malay text. The content was compared against the discharge instructions recommended by established guidelines. Results: 49 articles were eligible for the study. 26 of the articles met the criteria of understandability, and 3 met the criteria for actionability. The average readability level met the ability of average adult. Most of the discharge instructions focused on emergency symptoms, and none contained post-concussion features. Conclusion: Majority of the discharge instructions provided were appropriate for average people to read but difficult to understand and act upon. Important information was neglected in most discharge instruc- tions. Thus, revision and future development of mTBI discharge instruction should consider health literacy demand and cognitive ability to process such information.